As assessorias de imprensa das entidades fechadas de previdência complementar, segundo a proposta Martinez - Cruz, Maria do Céu Studart Matos (2006)
Public Relation in Privately-Held Pension Funds are the aim of this research, specifically in what concerns to its implantation and administration, in the light of Professor Maria Regina Esteves proposals. Theoretical sources with respect to Public and Private Pension Funds, Marketing, Communication, Communication Room and Public Relation are analyzed and presented. A field survey was undertaken, involving 83 Privately-Held Pension Funds, objecting quantitative perception. Conclusions points to the fact that most of Privately-Held Pension Funds do not have Public Relation. Nevertheless, organizations that possess them design structures and actions appropriated to the fulfillment of its institutional role, in line with Professor Martinez proposals. However, currently, the research returns the perception that Public Relation is still an area not well appraised by the Privately-Held Pension Funds.